EFEITO DA RADIAÇÃO ULTRAVIOLETA NA OXIDAÇÃO INDUZIDA DE AMIDO DE MANDIOCA - Hornung, Polyanna Silveira (2014)
The starch in its native form does not always have the appropriate physicochemical properties for processing. The chemical and physical changes has been widely studied in order to promote change in these characteristics. The work aimed to study the effects of ultraviolet radiation-induced oxidation of cassava starch. Cassava starch samples were oxidized with sodium hypochlorite and hydrogen peroxide in combination with exposure to ultraviolet light for 1 hour action. The samples were analyzed by Thermogravimetry and Derivative Thermogravimetry (TG / DTG), Differential scanning calorimetry (DSC), Viscoamilograph Analysis (RVA), X Ray Diffraction Powder, Non-contact Atomic Force Microscopy method (NC-AFM) and Color characteristics were analyzed by Reflectance Spectrophotometry. The modified samples showed higher thermal stability compared to the sample of cassava starch unmodified. The results of DSC of the samples modified with H2O2 showed little influence on the enthalpy of gelatinisation, but the modification with sodium hypochlorite considerably decreased the enthalpy of gelatinisation. Similarly, there was a decrease of the peak viscosity and final viscosity and setback, demonstrating the high degree of modification which occurred by treatment with NaClO. The micro-images revealed a significant increase of depressions and projections for the samples treated with NaClO and significant changes were obtained in the mean diameter of the granules of treated samples with H2O2. The two oxidation processes altered the relative crystallinity of the starch samples. The Colorimetry confirmed the bleaching action of NaClO and the mild action of H2O2. Therefore, the two-way modification had effects on the properties of cassava starch.